MiR-155 at the heart of oncogenic pathways - Czyzyk-Krzeska, MF (2013)
MicroRNAs are increasingly being recognized as oncogenes and tumor suppressors in cancer. MicroRNA-155 (miR-155) is an established oncomiR in breast cancer and regulates several pro-oncogenic pathways. In light of this, Chiang’s group has discovered a novel pathway regulated by miR-155. MiR-155 directly targets the VHL tumor suppressor and, by doing so, promotes the activity of HIF transcription factors and angiogenesis. This pathway appears to be particularly relevant in triple-negative breast cancer.